Comparison of efficacy and safety of different anticoagulation regimens in plasma exchange: A systematic review and meta-analysis. - Song Ren; Liming Huang; Yi Li; Yunlin Feng (PLoS ONE)
Background Extracorporeal line clotting during plasma exchange (PE) not only delays efficient treatment, but also cause great waste of nursing resources. There is a lack of comprehensive comparison of the efficacy and safety among different anticoagulation regimens in plasma exchange in literature. Methods A systematic search was performed in EMBASE, MEDLINE via PubMed, Cochrane Central Library, and CNKI. Studies that had compared at least two anticoagulation regimens in PE were considered eligible. The anticoagulative efficacy outcome was assessed by the occurrence of extracorporeal circuit clotting. The safety outcome was assessed by the occurrence of bleeding events, post-treatment APTT values, and post-treatment platelets counts. The risk of bias was assessed by the AHRQ tool. Mean differences or standardized mean differences with 95% confidence intervals (CIs) of continuous variables and risk ratios (RRs) with 95% CIs of categorical variables were pooled using a random-effects or a fixed-effects model as appropriate. Results In all, 7 studies with 1638 patients and 10951 sessions of PE treatment were included. Pooled results indicated the anticoagulative efficacy of UFH was better than that of saline flushing, yet did not differ with those of LMWH or RCA. Although the occurrence of bleeding events had no difference among different pairs of anticoagulation regimens, anticoagulation using UFH might lead to longer post-treatment APTT value and lower post-treatment platelet counts. Only one study was judged to have low risk of bias in each of the five domains in the AHRQ tool. Conclusions The current anticoagulation regimens are generally effective and well tolerated in PE; however, the number of included studies was too limited to draw definitive conclusions.